Change in glomerular volume and its clinicopathological impact after kidney transplantation. (July 2015) - Kobayashi, Akimitsu; Yamamoto, Izumi; Katsumata, Haruki; Yamakawa, Takafumi; Mafune, Aki; Nakada, Yasuyuki; Koike, Kentaro; Mitome, Jun; Miki, Jun; Yamada, Hiroki; Tanno, Yudo; Ohkido, Ichiro; et al.
Abstract: Background: Both immunological and non‐immunological etiologies affect graft function after kidney transplantation, including acute rejection, calcineurin inhibitor toxicity, and a recurrence of glomerulonephritis. Glomerular enlargement or glomerular sclerosis due to glomerular hyperfiltration related to increased renal blood flow is another cause. Although the glomerular volume in baseline biopsies predicts late allograft function, the relationship between allograft function and the annual changes in glomerular volume after kidney transplantation are unclear. Aim: We investigated changes in glomerular volume after kidney transplantation and their clinicopathological relationship. Methods: We enrolled 23 patients with stable kidney function without an episode of rejection or any complication resulting in a functional decrease in the graft. We measured glomerular volume (GV) using the Weibel–Gomez method and glomerular density (GD) using 0, 1 h biopsy samples as baseline controls and 1 yr biopsy samples and investigated the association between the changes in them and clinical parameters, including graft function, proteinuria, and renal hemodynamic markers, including effective renal plasma flow (ERPF) and filtration fraction (FF). The ERPF was calculated from a 99mTc‐mercaptoacetyltriglycine (MAG3) renogram. Results: The GV and ERPF increased significantly 1 yr after kidney transplantation. In contrast, proteinuria decreased significantly and Δproteinuria (1 yr – 1 month after transplantation) was correlated with ΔGV ( P < 0.05, rs = –0.467). Conclusion: Glomerular enlargement 1 yr after transplantation may be related to improved proteinuria. It is possible that glomerular enlargement serves as a renal adaptation after kidney transplantation.